Biological control of rice pests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Research aimed at developing fungal insecticides to combat the brown planthopper, Nilaparvata lugens, and the Malayan rice bug, Scotinophara coarctata, is being conducted at the International Rice Research Institute (IRRI) in the Philippines....